Development of the Methodological Framework for the Calibration and Validation of the Hydrodynamic Model of the Sewer System of the Faculty of Engineering and Applied Sciences - Paredes Méndez, Diego Fernando (2024)
Urban Drainage Systems (UDS) have existed since the Babylonian Empire. Its objective is to preserve and promote the public health, welfare, flood protection, water pollution. Population growth in urban areas, climatic change, ageing structures, produce failures in the sewer systems, and urban flooding. Therefore, in this research, a methodologic framework was developed to assess the hydraulic performance of an UDS in a pilot basin. By using three kinds of information, spatial, temporal and terrain, a number of products were generated such as: design rainfall, historic precipitation, dry weather flows and their patterns, topological network, land uses, DTM, DSM, ortophoto, subsequently a hydrodynamic 1D model was built. Calibration and validation of the model was carried out by employing hydrometeorological data that was registered in four sensors to measure depth, velocity of the flow and a gauge station that were implemented in the study area.